If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-6f-5=-10
We simplify the equation to the form, which is simple to understand
-6f-5=-10
We move all terms containing f to the left and all other terms to the right.
-6f=-10+5
We simplify left and right side of the equation.
-6f=-5
We divide both sides of the equation by -6 to get f.
f=0.83333333333333
| X^2=1/3x | | 80c+-2c=-59 | | log1/2^(x-3)=-4 | | .40+.10=.50(n+4) | | .40+.10=.50(n+4) | | -5-4x+7x=-8 | | 52=(4+y)-22 | | .40+.10=.50(n+4) | | 2/3(12)=1 | | 2/3(12)=1 | | 2/3(12)=1 | | 5(9-7)=25 | | -5-4x+7x=-8 | | 81/27•6-2 | | -3(a+1)-3=7 | | 6x+10-2x=2x+6 | | .006s=.18 | | x^2-15x+70=0 | | -7x+40=-2x+5 | | -14:23=2/7-1/7x | | 4y-1a=5a+6(3-1y) | | 9x=7+2 | | 7n-32=-32+8n-1n | | 4.5x+28=-10 | | 3x+2g=12 | | N/2-7=-6 | | 4/5(3x-5)=45 | | 14b^2-29b-15=0 | | 4/x=20/75 | | 1.5+.3r=-4.2 | | 1x*10/15=2 | | 8a=4a-4 |